2020
DOI: 10.5334/cstp.303
|View full text |Cite
|
Sign up to set email alerts
|

Still in Need of Norms: The State of the Data in Citizen Science

Abstract: This article offers an assessment of current data practices in the citizen science, community science, and crowdsourcing communities. We begin by reviewing current trends in scientific data relevant to citizen science before presenting the results of our qualitative research. Following a purposive sampling scheme designed to capture data management practices from a wide range of initiatives through a landscape sampling methodology (Bos et al. 2007), we sampled 36 projects from English-speaking countries. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 46 publications
0
63
0
Order By: Relevance
“…The complete description of research findings can be found in the journal article by Bowser et al (2020). In addition, as a complementary practical resource the TG offered a summary of recommendations in six areas of the data lifecycle.…”
Section: Findings Current Data Practices In Citizen Science and Recommentioning
confidence: 99%
See 1 more Smart Citation
“…The complete description of research findings can be found in the journal article by Bowser et al (2020). In addition, as a complementary practical resource the TG offered a summary of recommendations in six areas of the data lifecycle.…”
Section: Findings Current Data Practices In Citizen Science and Recommentioning
confidence: 99%
“…1 The interest was in evaluating CS practices throughout the data lifecycle. To that end, the Task Group (TG) conducted a survey of data collection, validation, curation, and management practices for a sample of 36 CS projects globally representing different research domains, types of CS practices, and regions (results published in Bowser et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…governance, data documentation, data access, data services, and data integration (Bowser et al, 2020).…”
Section: Anonymitymentioning
confidence: 99%
“…Data and knowledge resources generated through public participation represent the foundation of CS, often recognised as an important aspect of the open science agenda (Mirowski, 2018). However, recent evidence suggests that CS projects are sometimes failing to provide open access to research outputs and/or in proper formats (Bowser et al, 2020;Groom et al, 2017). What is unique to CS is, indeed, that the community of citizen scientists has an active stake in the production of data as co-producers (not only as taxpayers, as in the open access debate), which highlights extra ethical and legal challenges for knowledge access and reuse (Riesch & Potter, 2014).…”
Section: Knowledge and Technological Policy Knowledge Policymentioning
confidence: 99%
“…What is unique to CS is, indeed, that the community of citizen scientists has an active stake in the production of data as co-producers (not only as taxpayers, as in the open access debate), which highlights extra ethical and legal challenges for knowledge access and reuse (Riesch & Potter, 2014). At the same time, open data practices and data management policies may help to prevent misconceptions regarding data sharing (Bowser et al, 2020), increase project's success (Theobald et al, 2015), and motivate initial, continued, and renewed engagement in CS projects (De Vries et al, 2019). A crucial element for favouring data access and reuse is to implement explicit data management policies (Bowser et al, 2020) with standard licences and no restrictions on commercial usage, but requiring attribution and 'share alike' formats (Groom et al, 2017).…”
Section: Knowledge and Technological Policy Knowledge Policymentioning
confidence: 99%